STRATEGI PEMASARAN KERIPIK PISANG DALAM RANGKA MENCAPAI KETAHANAN PANGAN DI KECAMATAN CILONGOK, KABUPATEN BANYUMAS - PUTRI, DINDY DARMAWANTI; MULYANI, ALTRI; SATRIANI, RATNA (Universitas Sebelas Maret, 2012)
This research aim to make the banana chips marketting strategy formulation in Cilongok Region, Banyumas Regency.The location decided by purposive random sampling, and to decide the sampling of banana chips’s worker and retailer by simple random sampling that totaly 33 person. The methode that used to decide the marketting strategy by SWOT analysis. The research shows that the home industry on the first quadrant. The marketing strategy at this quadrant is growth orientedstrategy. This strategy consists of defend and increase the product quality, increase the service quality to the customers, increase the product quantity and market penetration, increase the capitals and promotion of local product widely.